Гіперандрогенія як чинник репродуктивних втрат - Семенюк, Л. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
The lesson presents the current data on the physiological role of androgens in women and pathological conditions that occur in violation of hormonal homeostasis dominated by androgens in women of reproductive AGES. Shows the close relationship between hyperandrogenism and reproductive losses.